Mathematics
las
11

How do I solve this using the elimination method

+1
(1) Answers
casiano710

Essentially, you multiply one row by a number and add it to another to elimate a variable. Multiplying the first equation by -2 and adding it to the second, we get -3y+4z=-13 Multiplying the first equation by -4 (because x*-4+4x=0) and adding it to the third, we get  -5y+13z=-28 We have 2 new equations -  -3y+4z=-13 -5y+13z=-28 Multiplying the first new equation by -5/3 and adding it to the second new one, we get -20z/3+13z=-65/3+28 solving for z, we get (-65/3+28)/(-20/3+13)=1. After that, it's easy to solve for y and x.

Add answer